The killer question - Hallett, Janice (Atria Books, 2025)
Janice Hallett, "the new queen of crime" (Electric Literature), returns with a fresh, edge-of-your-seat mystery that takes place at a pub's weekly trivia night, revealed through quiz categories, phone messages, and email correspondence. Sue and Mal Eastwood run an isolated rural pub called The Case is Altered where a weekly trivia game has revived its flagging fortunes--that is, until a body is found in the nearby river. Soon after, a mysterious new team arrives and shakes up the diverse field of regulars by scoring top marks in every round...every week. Meanwhile, Sue and Mal have a secret of their own. Before arriving here, they were caught up in a secret police operation which meant they had to leave town--and whatever happened back then seems to have finally caught up with them. Five years later, the pub lies derelict, and their nephew Dominic is determined to make a documentary about their story. What happened at this unassuming pub? And can a single question really kill?